2018
DOI: 10.4992/pacjpa.82.0_3am-042
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting of monetary rewards in children with ADHD and autism spectrum disorders

Abstract: 即時小報酬と遅延大報酬の選択場面において,前者を選好 することは衝動性,後者を選好することはセルフ・コントロ ールと呼ばれている。 このような選択場面における衝動性は, 報酬の主観的価値が遅延時間に伴って大きく割り引かれるこ とによって生じると考えられる (遅延割引:delay discounting) 。 遅延割引率は発達とともに変化し,定型発達児では年齢の上 昇に伴って低下する (衝動的選択が減少する) (空間ら, 2017) 。 一方,衝動性を症状に含む発達障害である,注意欠如・多動 性障害(Attention-Deficit/Hyperactivity Disorder: ADHD)の児 童は,定型発達児とは異なる遅延割引率を示すことが報告さ れている(Demurie et al., 2012) 。しかしながら我が国におい ては十分にデータが蓄積されていない。 そこで本研究では,空間らによって開発された簡易版遅延 割引質問紙を用いて,ADHD 児,および自閉症スペクトラム 障害(Autism Spectrum Disorder: ASD)児の遅延割引率を測定 することを試みた。また,日常場面における自己制御… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prevalence estimates of APD are difficult to determine based upon the fact that there is no universal agreement on diagnostic criteria. Prevalence ranges include anywhere from 2%–3% (Chermak & Musiek, 1997; Palfery & Duff, 2007) to 12% (DiMaggio & Geffner, 2003) and as high as 20% (Katz, 2005). Research on APD has not been without controversy, with multiple arguments in topics ranging simply from the title of the disorder (ASHA, 2005; Jerger & Musiek, 2000), to specific diagnostic criteria (Riccio et al, 2005) and skepticism regarding the source of the disordered modalities in question (Cacace & McFarland, 2006; Maerlender & Heath, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence estimates of APD are difficult to determine based upon the fact that there is no universal agreement on diagnostic criteria. Prevalence ranges include anywhere from 2%–3% (Chermak & Musiek, 1997; Palfery & Duff, 2007) to 12% (DiMaggio & Geffner, 2003) and as high as 20% (Katz, 2005). Research on APD has not been without controversy, with multiple arguments in topics ranging simply from the title of the disorder (ASHA, 2005; Jerger & Musiek, 2000), to specific diagnostic criteria (Riccio et al, 2005) and skepticism regarding the source of the disordered modalities in question (Cacace & McFarland, 2006; Maerlender & Heath, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the comorbidity of children diagnosed with both APD and ADHD is staggering. In a review of 425 children diagnosed with APD between the ages of 4–14 years, DiMaggio and Geffner (2003) noted that 84% of children evaluated for APD have confirmed or suspected ADHD. Riccio et al (1994) reported that at least 50% of children diagnosed with APD would also fit the diagnostic criteria of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, children with ADHD exhibit a strong bias towards small, immediate rewards over large, delayed rewards more frequently than typically developing (TD) children [10]. Ikegami et al [11] reported that Japanese children with ADHD and children with ASD showed steep discounting of monetary reward compared to TD children, and the discounting rate correlated with impulsive choice Brain Sci. 2023, 13, 758 2 of 14 tendencies in daily life.…”
Section: Introductionmentioning
confidence: 99%